2019
DOI: 10.1016/j.ijscr.2019.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic intramural hematoma of the right colon. A case report and review of the literature

Abstract: Highlights A very rare case of spontaneous colon hematoma has been reported. The rarity of our case of colon hematoma is due to the fact that it is idiopathic. The topic is still under discussion in the Literature since the pathophysiology remains still unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…The etiologies may include abdominal trauma, anticoagulant therapy, bleeding diathesis, or iatrogenesis [ 2 ]. Hematoma of the colon is much less frequent than hematoma in other segments of the gastrointestinal tract [ 3 ]. It can be supposed that it may be due to the protective role of the Teniae coli, which could prevent the diffusion of the hemorrhage in the bowel wall [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The etiologies may include abdominal trauma, anticoagulant therapy, bleeding diathesis, or iatrogenesis [ 2 ]. Hematoma of the colon is much less frequent than hematoma in other segments of the gastrointestinal tract [ 3 ]. It can be supposed that it may be due to the protective role of the Teniae coli, which could prevent the diffusion of the hemorrhage in the bowel wall [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“… Intestinal obstruction, hematochezia, Pallor, abdominal pain. No Intraoperative Not reported No No Right hemicolectomy Whole body edema, thrombocytopenia 14 Vecchio,2019 [ 3 ] 48 yr. M Spontaneous(idiopathic). Fever, abdominal pain, intestinal obstruction, mass in the right quadrants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first case of intestinal intramural hematoma was reported in 1855 by Thompson. Hughes et al reported about 109 cases of post-traumatic acute intramural hematoma in 1977, in which only 4% of cases were colonic intramural hematoma [4]. Since 1950, there were 16 cases with traumatic colonic intramural hematoma, which was more common in ascending colon [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, colonic intramural hematoma is very rare. The reason for the rarity in colon is supposedly due to the protective role of taenia coli, which can prevent blood diffusing in the bowel wall if there is a rupture of intramural vessels due to blunt trauma [4]. In traumatic acute colonic intramural hematoma, most of the reported cases were managed surgically.…”
Section: Introductionmentioning
confidence: 99%